عروض مختصرة - أسماء حسين ملكاوي (International Institute of Islamic Thought, 2011)
• القرآن والمتغيرات الاجتماعية والتاريخية، محمد أبو القاسم حاج حمد، بيروت: دار الساقي للطباعة والنشر، 2011م، 141 صفحة. • حوار حول: الإسلام هو القرآن وحده، محمد توفيق صدقي،رشيد رضا، طه البشري، جمع وتحقيق: هشام عبد العزيز، الرياض: جداول للطباعة والنشر والتوزيع، 2011م، 308 صفحة. • نحو نظرية قرآنية، محمد سلمان غانم، بيروت: دار الفارابي، 2011م، 504 صفحة. • الجدلية التاريخية في القرآن الكريم، عبد الله عيسى لحيلح، بيروت: منشورات زين الحقوقية، 2011م، 608 صفحة. • الله والإنسان في القرآن: علم دلالة الرؤية القرآنية للعالم، توشيهيكو إيزوتسو، ترجمة وتقديم: هلال محمد الجهاد، لبنان: المنظمة العربية للترجمة، 2007م، 387 صفحة. • الرحمانيةديموقراطية القرآن، محمد سلمان غانم، بيروت: دار الفارابي، 2008م، 246 صفحة. • الانتماء الحضاري والهوية الثقافية في ضوء عروبة القرآن أو الإسلام العربي، معالم في طريق الوحدة والتعايش والاعتدال لتدبّر القرآن وفهمه بلسان عربي مبين، علاء الدين المدرس، العراق: دار الرقيم، 2008م، 191 صفحة. • The Impact of the Qur'anic Verses on Mass Communication Practices: A Case Study, Aliy Abdulwahid Adebisi, Germany- LAP LAMBERT Academic Publishing, 2011, 72 pages. • The Dream in Islam: From Qur'anic Tradition to Jihadist Inspiration, Iain R. Edgar, Berghahn Books, 2011, 172 pages. • Qur'anic Hermeneutics: Al-Tabrisi and the Craft of Commentary (Routledge Studies in the Qur'an), Bruce Fudge, UK- Routledge; 1 edition, 2011, 176 pages. • Communication Strategies in the Qur'an: A Multidisciplinary Approach, Christian Tamas, Germany- LAP LAMBERT Academic Publishing, 2011, 252 pages. • Al-Ghazali and the Qur'an: One Book, Many Meanings (Culture and Civilization in the Middle East), Martin Whittingham, UK- Routledge; Reprint edition, 2011, 154 pages. • Beyond The Quran, Responding to Islam's Claim on Bible Prophecies. James Paul-Magidi, Longwood, FL- Xulon Press, 2011, 464 pages. • In Search of Our Origins: How the Quran Can Help in Scientific Research, Jamshed Akhtar, Seattle, WA- CreateSpace, 2010, 164 pagesز • Sounds of Qur'anic Recitation in Egypt: A Phonetic Analysis, Mohammed R. Elashiry See search results for this auAre you an author? Learn about Author Central (Author), Bruce Ingham (Foreword), New York- Edwin Mellen Pr, 2009, 352 pages. • Textual Criticism and Qur'an Manuscripts, Keith E. Small, Lanham, MD.: Lexington Books, 2011, 244 pages. • Life, The Universe & The Quran, Dr Saddique, Bloomington, IN.: AuthorHouse, 2011, 156 pages. • Women, War & Hypocrites: Studying the Qur'an, Robert A Campbell, Sydney: Cape Breton University Press, 2010, 244 pages. للحصول على كامل المقالة مجانا يرجى النّقر على ملف ال PDF  في اعلى يمين الصفحة.